High risk of obstructive sleep apnea among hypertensive patients at a selected tertiary care hospital - Subha, Sethu Thakachy; Lee, Heng Fah; Azhar, Fatin Liyana; Zulkeflee, Fatin Ahya (Universiti Putra Malaysia, 2023)
Introduction: Obstructive sleep apnea (OSA) is a sleep-related breathing disorder characterized by partial or complete obstruction of the upper airway, which causes desaturations and arousal. Various studies have shown that OSA is a major modifiable risk factor for hypertension. Untreated OSA is increasingly associated with cardiovascular and neurocognitive sequela. Thus, our study aims to determine the high-risk of obstructive sleep apnea among hypertensive patients at a tertiary care hospital in Malaysia. Methods: A cross-sectional study was conducted among hypertensive patients at a tertiary hospital in Malaysia. A validated Malay version of the Berlin Questionnaire was utilized along with other questions on sociodemographic characteristics and diabetes mellitus. Results: A total of 161 respondents were involved in the study. The mean age was 48.35 years and among these 75% were males and 25 % were females. The majority of respondents were of Malay ethnicity (78%), followed by Chinese (11%) and Indians (10%). Of these,18 % comprised of obese patients and 29.8% had diabetes mellitus. The prevalence of high-risk OSA among hypertensive patients was 18.0% (95% CI). High risk of OSA was found to be prevalent in the elderly age group (p<0.001), female gender (p<0.001), Indian ethnicity (p<0.001) and among diabetes mellitus patients (p<0.001). Conclusion: The study results illustrate the high risk of OSA among hypertensive patients with advancing age and diabetes mellitus. This study finding mandates these high-risk hypertensive patients should be screened for early diagnosis and timely treatment of OSA to prevent further cardiovascular risk, morbidity and mortality.